2013
DOI: 10.1371/journal.pone.0072533
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Ability of Non-Methylamine Osmolytes Present in Kidney Cells to Counteract the Deleterious Effects of Urea on Structure, Stability and Function of Proteins

Abstract: Human kidney cells are under constant urea stress due to its urine concentrating mechanism. It is believed that the deleterious effect of urea is counteracted by methylamine osmolytes (glycine betaine and glycerophosphocholine) present in kidney cells. A question arises: Do the stabilizing osmolytes, non-methylamines (myo-inositol, sorbitol and taurine) present in the kidney cells also counteract the deleterious effects of urea? To answer this question, we have measured structure, thermodynamic stability (ΔG D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 57 publications
(62 reference statements)
2
19
0
Order By: Relevance
“…Interestingly, it has also been reported there are other counteraction systems including ureamyo-inositol and urea-taurine at least under in vitro conditions (Khan et al, 2013). Thus under cellular conditions, the cells may probably counteract urea's effect on proteins and enzymes by employing multiple counteracting systems as supported by the arguments that counteracting osmolytes act independently on proteins, i.e., none of the osmolytes affects the efficacy of the other (Khan et al, 2013;Mello and Barrick, 2003).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 92%
See 3 more Smart Citations
“…Interestingly, it has also been reported there are other counteraction systems including ureamyo-inositol and urea-taurine at least under in vitro conditions (Khan et al, 2013). Thus under cellular conditions, the cells may probably counteract urea's effect on proteins and enzymes by employing multiple counteracting systems as supported by the arguments that counteracting osmolytes act independently on proteins, i.e., none of the osmolytes affects the efficacy of the other (Khan et al, 2013;Mello and Barrick, 2003).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 92%
“…Thus under cellular conditions, the cells may probably counteract urea's effect on proteins and enzymes by employing multiple counteracting systems as supported by the arguments that counteracting osmolytes act independently on proteins, i.e., none of the osmolytes affects the efficacy of the other (Khan et al, 2013;Mello and Barrick, 2003).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies showed synergistic interactions between amino acid and sugar stabilizers in thermal denaturation (Khan et al, 2013b) and between sucrose and glycine in pressure inactivation of an enzyme (Kidman and Northrop, 2005).…”
Section: Synergismmentioning
confidence: 96%